THE DEVELOPMENT OF PERSONNEL MANAGEMENT MANUAL BASE ON THE FOUR SANGAHAVATTHU OF BAN CHA-UAT SCHOOL UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Phliphol, Suparat; PhrakhruPhichitsupakarn; Yotharak, Maliwan (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of this research article were to 1) study the condition of personnel management, 2) develop a personnel management manual based on the principles of the Four Saṅgahavattthu, and 3) present a personnel administration manual based on the principles of the Four Saṅgahavattthu of Ban Cha-uat School, under the Office of the Primary Educational Service Area of Nakhon Si Thammarat Area 3. This research was qualitative. Data were collected through in-depth interviews with 15 relevant persons, in-depth interviews with 5 experts to draft the manual, and focus groups with 7 qualified persons to assess the appropriateness, feasibility, and usefulness. Qualitative data were analyzed through content analysis. The results of the study were as follows: 1) The personnel management situation in Ban Cha-uat School was found to be a large school. The teaching load and other workloads were quite high, causing teachers to change every year. The unclear personnel management structure affected the work of new personnel, causing many problems and obstacles. Therefore, it was necessary to have a personnel management guideline with clear principles and guidelines for work. 2) The development of personnel management manual based on the Four Saṅgahavattthu of Ban Cha-uat School, under the Office of the Primary Educational Service Area of Nakhon Si Thammarat Area 3, which included the following: (1) Recruitment and appointment, (2) Manpower planning and position determination, (3) Enhancement of efficiency in civil service, (4) Discipline and discipline maintenance, (5) Resignation from civil service, (6) Teacher registration, (7) Personnel development and performance evaluation of teachers and personnel, (8) Various types of leave, official travel/permission request by applying the principles of the Four Saṅgahavattthu, consisting of (1) Dna (giving help to others), (2) Piyavc (using polite words), (3) Atthaciriy (sacrifice, not being selfish), and (4) Samnattat (consistent and appropriate behavior) by conducting appropriately and relying on the participation of all sectors. 3) The manual for personnel management according to the principles of the Four Saṅgahavattthu of Ban Cha-uat School, under the Office of the Primary Educational Service Area of Nakhon Si Thammarat, Area 3, found that it was appropriate, possible, and useful for personnel management according to the principles of the Four Saṅgahavattthu of the educational institution.